Review Of Natural Compounds And Medicinal Chemistry Approaches In Drug Development - Saeful Amin; Hilna Putri Herlina; Wulandari Wulandari; Miela Agustin (CV. AFDIFAL MAJU BERKAH, 2026)
The increasing prevalence of degenerative and infectious diseases has encouraged the development of more effective, selective, and safer therapeutic agents. Natural compounds and medicinal chemistry approaches have demonstrated considerable potential in modern drug discovery due to their diverse pharmacological activities and structural complexity. This study aims to review the role of bioactive natural compounds and computational approaches in contemporary drug development. The method employed was a literature review based on recent scientific publications discussing medicinal chemistry, molecular docking, quantitative structure–activity relationship analysis, artificial intelligence-assisted drug design, and nanoformulation strategies. The findings indicate that several natural compounds, particularly flavonoids and quercetin, exhibit promising anticancer, antidiabetic, antioxidant, and antibacterial activities through interactions with various biological targets. Computational approaches such as molecular docking, virtual screening, predictive modeling, and deep QSAR were shown to improve the efficiency of lead identification and molecular optimization. Furthermore, nanoformulation systems contribute to enhancing bioavailability, molecular stability, and therapeutic effectiveness of bioactive compounds. Despite these advantages, challenges including compound complexity, ADMET limitations, and the necessity for experimental validation remain important considerations in drug development. In conclusion, the integration of natural compounds, medicinal chemistry, and computational technologies provides significant opportunities for accelerating and optimizing modern drug discovery and development.